Tomato Cultivar Selection Considerations for Open-Field and Protected Culture in North Florida - Blake R. Thaxton; Robert C. Hochmuth (EDIS, 2016)
Tomatoes represent one of the most popular vegetables grown in protected culture such as greenhouses, high tunnels, or shade houses. Selecting the correct cultivar of tomato is critical and varies depending on the intended season, type of protected structure, training system, expected insect and disease pressure, post-harvest handling techniques, and intended market. This 7-page fact sheet will focus on the key factors affecting the cultivar selection decisions for growing and selling tomatoes in north Florida. Written by Blake R. Thaxton and Robert C. Hochmuth, and published by the Horticultural Sciences Department, December 2015.